How do interregional spillovers influence the distribution of technology? The case of Chinese manufacturing. Issue 2 (3rd April 2018) - Jiang, Xuemei; Lu, Xiaolin; Xu, Jian
ABSTRACT: The Chinese economy displays considerable inequality across regions. In this paper, we analyzed the distribution of intermediate input shares in China. We use regional input–output tables from 2007 and find that regions with higher GDP per capita generally had higher input shares, regardless of sector. Then, using intermediate input shares as a proxy of technology, we analyzed the pattern of regional technology distributions across manufacturing sectors as well as the extent of interregional technology spillovers. Our results indicate that interregional backward spillovers have significantly positive impacts on the shape of the technology distributions in eastern (coastal) regions. By contrast, the vertical spillovers of the central and western regions are largely dominated by intra-regional forward effects. Our results suggest that the shift of Chinese manufacturing from coastal to inland regions with lower production costs cannot reduce the imbalance among regions unless the technology gap is narrowed.